2014
DOI: 10.5588/ijtld.14.0228
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of tuberculosis case finding in private health care facilities in a South Indian district

Abstract: The proportion of extra-pulmonary cases was higher in the medical college and nursing homes and that of retreatment cases was lower than in the RNTCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Bone TB has been suggested as an important cause of vertebral osteomyelitis and it is a common site of EPTB. 21 A study conducted in Private Medical College in India revealed that about 83% of all cases diagnosed were EPTB. 21 This could be due to availability of expertise and facilities for EPTB diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone TB has been suggested as an important cause of vertebral osteomyelitis and it is a common site of EPTB. 21 A study conducted in Private Medical College in India revealed that about 83% of all cases diagnosed were EPTB. 21 This could be due to availability of expertise and facilities for EPTB diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…21 A study conducted in Private Medical College in India revealed that about 83% of all cases diagnosed were EPTB. 21 This could be due to availability of expertise and facilities for EPTB diagnosis. MDR-TB cases were detected in 3.17% patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this is likely to be low, as the selected DMCs are located at the headquarters of their respective TUs, where the majority of the district's PPs have their practice. Another limitation is that as data were extracted from DMC laboratory registers, referred cases who did not reach the DMCs were not captured, hence potentially leading to an underesti- 21 It should be noted, however, that at the time of the study histopathology was available only in the private sector in the district, making referral to the RNTCP for the diagnosis of extra-pulmonary TB not meaningful to explore. The WHO recommends that the source of referral and place of treatment be routinely recorded and reported to assess PSP participation in national TB programmes.…”
Section: Discussionmentioning
confidence: 99%